"And men ne'er spend their fury on a child" – killing children in Shakespeare's early histories. (3rd July 2017) - Harper, Elizabeth
ABSTRACT: This essay offers a fresh reading of Shakespeare's preoccupation with the sacrifice of children to dynastic futurity in the first tetralogy, the three parts of Henry VI and Richard III . It shows how these plays blend psychological, metaphysical and political perspectives and veer from a world of disenchanted politics into the claustrophobic blood-feuding of classical tragedy. It argues that children in this world exist as figures in someone else's play; as royal pawns in adult power games they are the fragile vessels of dynastic ambition. The fate of children offers a spectacle of English history as a tragedy of failed succession, a viewpoint which not only politically troubles triumphant Elizabethan providentialism, but also reminds us of the existential role that children play in negotiating the fear of human mortality. It rereads Richard III against the earlier tetralogy to show how the ontological vulnerability of Richard is connected to the killing off of heirs. These dead children reveal the tragic precariousness of mortal existence precisely because they are the mystified objects of future promise.